Human epidermal growth factor receptor 2 testing in gastric cancer: Recommendations of an Asia‐Pacific Task Force. Issue 4 (16th September 2014) - Kim, Kyoung‐Mee; Bilous, Michael; Chu, Kent‐Man; Kim, Beom‐Su; Kim, Woo‐Ho; Park, Young Soo; Ryu, Min‐Hee; Sheng, Weiqi; Wang, John; Chao, Yee; Ying, Jianming; Zhang, Sheng
Abstract Human epidermal growth factor receptor 2 (HER2) testing in gastric and gastroesophageal junction cancer is an evolving area in clinical practice that has particular relevance to Asia‐Pacific countries, which face a high incidence of these diseases. A growing body of evidence demonstrates that HER2‐targeted therapy improves survival for patients with HER2‐positive advanced disease, and drives the need for high‐quality testing procedures to identify patients who will respond to treatment. However, various factors challenge day‐to‐day testing of gastric specimens in these countries, to a degree greater than that observed for breast specimens. Recommendations for HER2 testing of gastric cancer specimens were published as a result of the Trastuzumab for Gastric Cancer (ToGA) trial. The guidelines proposed in this manuscript build on these recommendations and emphasize local testing environments, particularly in Asia‐Pacific countries. A multidisciplinary task force comprising experts from Asia‐Pacific who actively work and provide education in the area was convened to assess the applicability of existing recommendations in the Asia‐Pacific region. The resulting recommendations reported here highlight and clarify aspects of testing that are of particular relevance to the region, and notably emphasize multidisciplinary collaborations to optimize HER2 testing quality.